Pentingnya Pengetahun Perpajakan dan Kesadaran Masyarakat dalam Membayar Pajak Guna Membantu Kestabilan Ekonomi di Indonesia - Fathiya Syahidah Nasution; Dian Zahra Syahfitri Lubis; Hikmah Indri Yani Harahap; Dini Vientiany (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2024)
The purpose of this research is to find out the importance of taxation knowledge and public awareness in paying taxes to help stabilize the economy in indonesia. taxes are mandatory levies in the form of money that comes from the people and is given to the state government. So, taxes are an obligation for all Indonesian people so that the state is able to gain revenue and carry out development. this research uses qualitative by analyzing previously published documents on the research topic being studied. By having sufficient knowledge about taxation, people will better understand the importance of paying taxes as an obligation that must be fulfilled for the development of the country. In addition, public awareness in paying taxes will also help in reducing the level of tax violations and increasing tax compliance. Therefore, the role of education and socialization regarding taxation and increasing public awareness in paying taxes needs to be continuously improved to achieve the goal of optimal tax revenue in Indonesia.